Short-Run Gains, Long-Run Trade-Offs: Revisiting FDI, Trade Openness, and Renewable Energy in ASEAN Economic Growth - Pratiwi, Dwi Sartika Lingga; Rohima, Siti; Bashir, Abdul (Economics, Business, Accounting & Society Review, 2025)
ASEAN economies have undergone significant structural transformation, driven by increasing foreign direct investment (FDI), trade openness, and renewable energy adoption. This study investigates the long-run relationship among these variables and their effects on economic growth across ten ASEAN countries from 1998 to 2022. Using panel data and an Autoregressive Distributed Lag (ARDL) approach, this research examines both short-run and long-run dynamics. The long-run estimation reveals that FDI negatively affects economic growth with a coefficient of -0.486, indicating crowding-out effects and institutional inefficiencies. Similarly, trade openness shows a significant negative impact (-0.010), reflecting vulnerabilities related to external shocks and structural imbalance. In contrast, renewable energy consumption exerts a positive and significant influence (0.224), supporting the green growth hypothesis. Short-run results differ, with both FDI and trade openness positively influencing growth, while renewable energy remains statistically insignificant. The model confirms long-run cointegration among variables, validating their interdependence in shaping growth trajectories. These findings highlight that while FDI and trade liberalization may yield short-term gains, their long-term benefits depend on institutional quality and policy design. The study contributes to policy discourse by emphasizing the strategic importance of investing in renewable energy infrastructure and enhancing domestic absorptive capacity to sustain inclusive and resilient economic growth in ASEAN.